Manufactured Housing - Wentling, James (Designing a Place Called Home, 2017)
I would like to briefly address manufacturedManufactured housing and modular housingModular housing as a segment of new home production, particularly with affordable homes. For purposes of this discussion, I will only address manufactured housing that is substantially factory-built as modules, hauled by trailer to the site, and assembled with field labor. And in keeping with the scope of this book, the discussion will only address low-rise applications of manufactured housing, though still acknowledging that recently there have been tremendous inroads toward mid- and high-rise application of manufactured housing in urban settings.